“Comparativo de cinco variedades de lechuga (lactuca sativa L.) cultividades bajo condiciones agroecológicas de la provincia de Lamas” - Gebol Reategui, Giovanna (2010)
This paper titled "Comparison of five varieties of lettuce (Lactuca sativa L.) grown under ecological conditions of the Province of Lamas was held in order to evaluate and assess the agronomic performance of five varieties of lettuce (Lactuca sativa L . ) agro-ecological conditions in the province of Lamas, and to conduct economic analysis. The cultivars were: White Boston, Parris !stand Cos, Grand Rapids, Alface venerable, Great Lakes 659 (control), which was used to design randomized complete block (BCCA), with an area of tropical dry forest voda (bs-T) and a soil texture class sandy loam with a slightly acidic pH. Befare planting was carried out biosolarización. The results indicate that the introduced varieties Alface Veneranda and Paris lsland Cos, the higher yields obtained with 17,523 and 16,483 tonnes I ha, variety Grand Rapids, had an intermediate behavior, taking the last places White varieties Great Boston and the control Lake 659). All varieties introduced and studied in this first trial showed adaptability, adequate profitability, standing Alface Veneranda introduced varieties and París lsland Cos with a benefit l cost ratio of 4.08 and 3.85, respectively. The variety Great Lakes 659, still has good agronomic adaptation to ecological conditions of the province of Lamas, which still deserves further prometed Key Words: Comparative, varieties, agro-ecological conditions, development, cost / benefit ratio.